2015
DOI: 10.1520/jte20130144
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Evaluation of Warm SMA Using Wax-Based WMA Additive in Korea

Abstract: Conventional stone mastic asphalt (SMA) is being increasingly used in highways and expressways because it provides high rutting resistance, good skid resistance, and noise reduction for heavily trafficked roads. However, the conventional SMA mixture requires high mixing and compacting temperatures to create a suitable coating between the polymer-modified asphalt and large size of aggregate. Warm-mix asphalt (WMA) technology is being extended to provide significant economic benefits when applied to heat sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…This study examined the adaptability of PSMA with a nominal maximum aggregate size (NMAS) of 13mm (13mm PSMA), and this is the popular combination through the blends presently utilized in BRT routes in Seoul, in order to support the sustainability pavement growth for the bus station. As a result of preliminary laboratory testing, it revealed that the 10mm PSMA demonstrated the highest plastic deformation resistance while maintaining other durability characteristics, thus, this mixture is the featured mix design used to release the burden on the conventional PSMA 13mm [6,7]. To achieve this goal, a multitude of experimental tests, comprising the dynamic modulus test and Hamburg wheel tracking test, were carried out to confirm the effectiveness of this combination.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study examined the adaptability of PSMA with a nominal maximum aggregate size (NMAS) of 13mm (13mm PSMA), and this is the popular combination through the blends presently utilized in BRT routes in Seoul, in order to support the sustainability pavement growth for the bus station. As a result of preliminary laboratory testing, it revealed that the 10mm PSMA demonstrated the highest plastic deformation resistance while maintaining other durability characteristics, thus, this mixture is the featured mix design used to release the burden on the conventional PSMA 13mm [6,7]. To achieve this goal, a multitude of experimental tests, comprising the dynamic modulus test and Hamburg wheel tracking test, were carried out to confirm the effectiveness of this combination.…”
Section: Methodsmentioning
confidence: 99%
“…The concept from earlier work [6,7] was employed to generate the aggregate's particle size for this investigation. The materials included lime filler, fine aggregate (0.075 -4.75 mm), and coarse aggregate with distribution sizes varying between 4.75 and 12.5 mm.…”
Section: Methodsmentioning
confidence: 99%
“…Authors determined viscoelastic properties, moisture susceptibility, fatigue resistance, rutting resistance at high temperature, and crack resistance at a low temperature of both samples. They reported that WMA variants demonstrated better performance in these performance parameters in comparison to conventional SMA variants (Kim et al, 2015). In addition, SMA-WMA is more environmentally friendly than conventional SMA in terms of economic competition (Leng, Al-Qadi, & Cao, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…They are therefore both essential elements for the production of a bituminous mixture suitable for traffic, and for durability. In both elements, important improvements have been made in this research to obtain a product of maximum quality, differentiable from the conventional one [34].…”
Section: Introductionmentioning
confidence: 99%